The hidden Niemann-Pick type C patient: clinical niches for a rare inherited metabolic disease. (4th May 2017) - Hendriksz, Christian J.; Anheim, Mathieu; Bauer, Peter; Bonnot, Olivier; Chakrapani, Anupam; Corvol, Jean-Christophe; de Koning, Tom J.; Degtyareva, Anna; Dionisi-Vici, Carlo; Doss, Sarah; Duning, Thomas; Giunti, Paola; et al.
Abstract: Background: Niemann-Pick disease type C (NP-C) is a rare, inherited neurodegenerative disease of impaired intracellular lipid trafficking. Clinical symptoms are highly heterogeneous, including neurological, visceral, or psychiatric manifestations. The incidence of NP-C is under-estimated due to under-recognition or misdiagnosis across a wide range of medical fields. New screening and diagnostic methods provide an opportunity to improve detection of unrecognized cases in clinical sub-populations associated with a higher risk of NP-C. Patients in these at-risk groups ("clinical niches") have symptoms that are potentially related to NP-C, but go unrecognized due to other, more prevalent clinical features, and lack of awareness regarding underlying metabolic causes. Methods: Twelve potential clinical niches identified by clinical experts were evaluated based on a comprehensive, non-systematic review of literature published to date. Relevant publications were identified by targeted literature searches of EMBASE and PubMed using key search terms specific to each niche. Articles published in English or other European languages up to 2016 were included. Findings: Several niches were found to be relevant based on available data: movement disorders (early-onset ataxia and dystonia), organic psychosis, early-onset cholestasis/(hepato)splenomegaly, cases with relevant antenatal findings or fetal abnormalities, and patients affected by family history, consanguinity, and endogamy. Potentially relevant niches requiring further supportive data included: early-onset cognitive decline, frontotemporal dementia, parkinsonism, and chronic inflammatory CNS disease. There was relatively weak evidence to suggest amyotrophic lateral sclerosis or progressive supranuclear gaze palsy as potential niches. Conclusions: Several clinical niches have been identified that harbor patients at increased risk of NP-C.